Epigenetic Regulation of CD133 in Gastrointestinal Stromal Tumors. Issue 5 (7th April 2017) - Geddert, Helene; Braun, Alexander; Kayser, Claudia; Dimmler, Arno; Faller, Gerhard; Agaimy, Abbas; Haller, Florian; Moskalev, Evgeny A.
Abstract: Objectives: This study ascertained the regulation of the stem cell marker CD133 and its potential applicability for prognostication of gastrointestinal stromal tumors (GISTs). Methods: A total of 95 resected GISTs were included in the study. CD133 protein expression was assessed immunohistochemically on tissue microarrays. Methylation percentage was quantified by pyrosequencing. Gene expression in cell lines GIST48b and GIST882 upon treatment with DNA demethylation agent 5-aza-2′-deoxycytidine was analyzed by quantitative polymerase chain reaction. Results: The expression of hypermethylated CD133 could be reactivated in the GIST cell line upon hypomethylation with the drug. Similarly, in patient material, CD133 methylation percentage correlated inversely with the protein expression and reflected tumor size with hypermethylation in small (<2 cm) tumors and virtually no methylation in large (>10 cm) GISTs. The gene's methylation percentage and expression level were clearly specific to anatomic sites and distinct driver mutations. KIT -mutant gastric GISTs exhibited significantly lower methylation degrees and concomitant high CD133 protein abundance compared with KIT -mutant GISTs from the small intestine. CD133 hypermethylation was documented in PDGFRA -mutant gastric GISTs along with low CD133 expression compared with KIT -mutant gastric GISTs. High CD133 expression was a prognosticator of shorter disease-free survival in all patients. In a subgroup of KIT -mutant gastric GISTs, low CD133 methylation degree was correlated with a shorter disease-free survival. Conclusions: Our results strongly suggest epigenetic regulation of CD133 expression by promoter methylation in GISTs. Pending further validation studies, high abundance of the protein can serve as a marker for malignant GISTs.